Physico-Chemical Factors Affecting thr formation of Emulsion - Pandey, I.P.; Sharma, Kanchan; Rawat, T.S. (Asian Journal of Chemistry, 2010)
The interfacial tension was regarded as a very important factor in determining the stability and the particle size of emulsions. It is now recognized that the work done in creating new interfaces is only a part of the interfacial tension promoting the disruption of the bulk interfaces, but the real importance of the emulsifier lies in the profound changes, especially of the electrical double layers, near the interfaces. The change in the interfacial tension is a readily measurable manifestation of the changes that have taken place in the nature of the interface.